APPLICATIONS ILLUSTRATED DICTIONARY INDONESIA - ENGLISH FOR CHILDRENS USING MACROMEDIA FLASH MX - Dicky Hidayat; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2006)
On Scientific Writing this author takes the title Applications Indonesian Picture Dictionary - English for Childrens. Because at this time a good mastery of foreign languages is needed, so we can follow the development of more advanced age. And this application can be used as one means of supporting the process of learning and teaching English to children - children in the Nursery kids. Multimedia program used to manufacture this illustrated dictionary application is using Macromedia Flash MX with vector graphics technology that describe images, lines, and curves, so that its size can be tailored to the needs of users without affecting the quality of the image. Macromedia Flash MX has many advantages or new facilities as compared with the previous Flash version. Element - the element used is text, images, and sounds.